The role of Glamping's attributes in a touristic experience: case study - Liberato, Pedro (2019)
This article intends to contribute to the deepening of scientific knowledge on the importance of glamping attributes. Glamping emerges as an innovative concept, capable of combining the advantages of camping, making up for the negative issues traditionally associated with it. This topic is justified by the growing trend around the world, which may serve to withdraw camping from the stagnation stage where it is. The present study aims to fill a significant lack of scientific material about glamping in Portugal and to identify the importance given to the attributes that define this concept: Nature, Accommodation, Gastronomy, Service and Experience. This way, focusing on the campsites in Porto’s Metropolitan Area (PMA), in the North of Portugal, data was collected through an original questionnaire, obtaining a convenient sample of 201 campers. The overall goal of this study is to identify the attributes that define the concept of glamping. The partial objectives are: to assess which of the attributes of glamping collects the greatest importance by the campers at Porto’s Metropolitan Area and to draw the profile of the potential user of the glamping in Porto’s Metropolitan Area. The elaboration of these objectives was supported in the understanding of the comments made by users of glamping experiences on the web that helped to identify the key attributes which define the scope and dimensions to this new concept (Brochado & Brochado, 2016). The studies of Gursoy & Chen (2012) had already addressed the reasons that influence the choice of a campsite, where they found some of these coincidental arguments with the concept of glamping. Regarding the analysed attributes, the one which collected the highest value of importance was the attribute related to the questions about "Nature", followed by the attributes "Service" and "Accommodation_Amenities". This finding confirms the basis of glamping concept. The profile of the user of this concept was suggested through descriptive analysis. It was also concluded that the importance attributed to the service increases according to the amount willing to pay by the camper, per night in a glamping unit.